Determinants of Adolescents’ Happiness in Iceland - Laufey Fríða Guðmundsdóttir 1984- (2012)
Happiness has recently received increased attention from both researchers and policy makers. The determinants of happiness in adult life have been well explored in the last decades. The determinants of children’s and adolescents’ happiness have been less studied. The aim of this study was to explore the relations between socio-demographic factors and happiness among Icelandic adolescents as well as finding which factors are the best predictors for adolescents’ happiness. Data from the Icelandic Centre for Social Research & Analysis were used in this analysis. A sample of 2000 Icelandic adolescents aged 14 to 15 years in 9th and 10th grade was analysed. The main results show that 86.6% of Icelandic adolescents describe themselves as happy. Loneliness, physical health, how much time they spend with their parents and religiousness are strong predictors of Icelandic adolescents’ happiness. The findings will hopefully give a better understanding on which factors are most important for adolescents’ happiness which might be of interest to policy makers, parents and others who have happiness and well-being of Icelandic adolescents in mind. Key words: happiness, well-being, adolescents, physical health, religiousness